Auroral Processes at the Giant Planets: Energy Deposition, Emission Mechanisms, Morphology and Spectra - Badman,SV; Branduardi-Raymont,G; Galand,M; Hess,SLG; Krupp,N; Lamy,L; Melin,H; Tao,C (Space Science Reviews, 2014)
The ionospheric response to auroral precipitation at the giant planets is reviewed,using models and observations. The emission processes for aurorae at radio, infrared, visible,ultraviolet, and X-ray wavelengths are described, and exemplified using ground- andspace-based observations. Comparisons between the emissions at different wavelengths are made, where possible, and interpreted in terms of precipitating particle characteristics oratmospheric conditions. Finally, the spatial distributions and dynamics of the various componentsof the aurorae (moon footprints, low-latitude, main oval, polar) are related to magnetosphericprocesses and boundaries, using theory, in situ, and remote observations, withthe aim of distinguishing between those related to internally-driven dynamics, and thoserelated to the solar wind interaction.